2002
DOI: 10.1364/ao.41.000700
|View full text |Cite
|
Sign up to set email alerts
|

Thermally assisted recording of holographic gratings in semicrystalline azobenzene-containing polymers

Abstract: We examine optically induced birefringence in semicrystalline azopolymer films that are held at glass-transition temperature Tg. The birefringence increases markedly after interception of the pump beam; the saturation value depends on exposure time. In addition, the induced birefringence is completely erased by irradiation with a circularly polarized beam at Tg. Using this thermally assisted method, we demonstrate the holographic recording of a test image. The intensity of the diffracted beam also increases af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We have reported that a thermally assisted recording can enhance Fourier transform holograms in semicrystalline azo polymer films. 19) Photocontrollability would, therefore, enable the enhancement of Fourier transform holograms thermally.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that a thermally assisted recording can enhance Fourier transform holograms in semicrystalline azo polymer films. 19) Photocontrollability would, therefore, enable the enhancement of Fourier transform holograms thermally.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) Azobenzene functionalized polymers are known to allow large-scale mass transport upon light irradiation and to result in the formation of surface relief. Although technical development of high-density data storage based on magnetic media is undoubtedly conspicuous, it is stated that there is a practical upper limit on recording density of about 1 TB/inch 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, thermal treatments as well as blue and red light illuminations can modify that response in a significant way. [13][14][15][30][31][32] We have tried several conditions, and selected those that give high and stable values for the diffracted intensity of volume holographic gratings. After an initial annealing of the films at 80 C for 1 min, they were irradiated for 5 s with a single circularly polarized 488 nm light beam (2 W/cm 2 ) to erase any previously stored information.…”
mentioning
confidence: 99%